Pattern of glomerular disease in a tertiary care hospital in Nepal: A Shree Birendra Hospital experience - Sharma, A; Deo, RK; Shahi, RR (Journal of College of Medical Sciences-Nepal, 2012)
The incidence of renal diseases varies greatly in various parts of the world. Percutaneous renal biopsy is an important procedure for many patients with renal disease. This hospital based retrospective study evaluated the pattern of various glomerular diseases in Shree Birendra hospital. Hospital records were searched for all the patients undergoing renal biopsy for all indication and patient profile and histopathological examination record were obtained. All the patients undergoing renal biopsy for any cause from January 2007 to December 2010 were included in the study. A total of 46 patients underwent renal biopsy in the study period. The number of patients in the various age groups were - <16 years – 5 patients, 16-50 years – 34 patients and > 50 years – 7 patients. The number of male and female patients was 34 and 12 respectively. Major indication for undergoing renal biopsy in this study was Nephrotic Syndrome (n=29, 63%), followed by RPGN (n=8, 17%), Persistent proteinuria (n=6, 13%) and Nephritic syndrome (n=3, 7%). The most common histopathological diagnosis in the study was Membranous nephropathy (n=10, 22%), followed by Focal Segmental Glomerulosclerosis (n=9, 20%), Membranoproliferative glomerulonephritis (n=9, 20%) and Minimal change disease (n=6, 13%). USG guided renal biopsy is safe in adults and is a very useful tool for the diagnosis of renal disease. The pattern of glomerular disease varies in different settings. There is a need for further evaluation of glomerular disease with larger sample size to determine the pattern of glomerular disease in Nepal. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 48-52 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6742